2021
DOI: 10.46300/9109.2021.15.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Historical Documentary Films as Information Technology in Improving Student Learning Outcomes

Abstract: This study aims to determine the effectiveness of documentary film media on the Dutch East Indies colonial history in Indonesia on student learning outcomes. History learning is a crucial subject in shaping students’ character and nationalism. Dutch East Indies colonialism is one of the topics in high schools in Indonesia. This study used a quasi-experimental research model involving 35 students in the experimental group and 36 students in the control group, with a nonequivalent pretest-posttest control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This finding is reinforced by previous research stating that documentary films can improve learning outcomes (Adi et al, 2021;Gero et al, 2019;Maskun et al, 2021). The use of proclamation documentary films on critical thinking skills and learning outcomes (Gero et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This finding is reinforced by previous research stating that documentary films can improve learning outcomes (Adi et al, 2021;Gero et al, 2019;Maskun et al, 2021). The use of proclamation documentary films on critical thinking skills and learning outcomes (Gero et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
“…Students' critical thinking skills differ before and after utilizing documentary film media in geography subjects (Herzon et al, 2018;Sari et al, 2017). Even if this medium is applied as in film, Dutch colonialism in documentary films is undoubtedly used as an alternative to solve the problem (Maskun et al, 2021). Preservice teachers in primary school inquiry with historical documentary films who concluded that by designing an inquiry exercise with documentaries that present a clear counter-narrative of the US Civil Rights Movement, teacher educators could challenge dominant racial narratives while encouraging recognition of pre-service teacher perspectives, expanding their understanding of historical matters, and encourage empathy for the motives and experiences of others (Buchanan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We can find examples of the use of film and documentary as educational strategies for children with learning disabilities with positive results [55]. Additionally, some studies have reported an improvement of the academic score of students in secondary schools with the integration of audiovisual materials [56,57]. Other research works have explored and confirmed the effectiveness of the documentary not only for the academic public but the general audience [50], reporting an increasing interest in scientific themes.…”
Section: The Audiovisual Methods and Documentary Film As Tools For Sc...mentioning
confidence: 99%
“…Previous research results have illustrated that the Aqeedah Akhlak curriculum can be developed through Islamic extracurricular activities (Mahmudah et al, 2021). In addition, the application of character education can also be integrated with subjects through lesson planning (Maskun et al, 2015). The integrated subjects are expected to be tools and opportunities for students to develop various characters (Agung, 2018).…”
Section: Introductionmentioning
confidence: 99%